In vitro evaluation of endothelial progenitor cells from adipose tissue as potential angiogenic cell sources for bladder angiogenesis. - Liuhua Zhou; Jiadong Xia; Xuefeng Qiu; Pengji Wang; Ruipeng Jia; Yun Chen; Bin Yang; Yutian Dai (PLoS ONE, 2015)
Autologous endothelial progenitor cells (EPCs) might be alternative angiogenic cell sources for vascularization of tissue-engineered bladder, while isolation and culture of EPCs from peripheral blood in adult are usually time-consuming and highly inefficient. Recent evidence has shown that EPCs also exist in the adipose tissue. As adipose tissue is plentiful in the human body and can be easily harvested through a minimally invasive method, the aim of this study was to culture and characterize EPCs from adipose tissue (ADEPCs) and investigate their potential for the neovascularization of tissue-engineered bladder. Adipose stromal vascular fraction (SVF) was isolated and used for the culture of ADEPCs and adipose derived stem cells (ADSCs). After SVF was cultured for one week, ADEPCs with typical cobblestone morphology emerged and could be isolated from ADSCs according to their different responses to trypsinization. Rat bladder smooth muscle cells (RBSMCs) were isolated and cultured from rat bladder. RBSMCs exhibited typical spindle-shaped morphology. ADEPCs had higher proliferative potential than ADSCs and RBSMCs. ADEPCs stained positive for CD34, Stro-1, VEGFR-2, eNOS and CD31 but negative for α-SMA, CD14 and CD45. ADSCs stained positive for CD34, Stro-1 and α-SMA but negative for VEGFR-2, eNOS, CD31, CD14 and CD45. RBSMCs stained only positive for α-SMA. ADEPCs could be expanded from a single cell at an early passage to a cell cluster containing more than 10,000 cells. ADEPCs were able to uptake DiI-Ac-LDL, bind UEA-1 and form capillary-like structures in three-dimensional scaffolds (Matrigel and bladder acellular matrix). ADEPCs were also able to enhance the human umbilical vein endothelial cells' capability of capillary-like tube formation on Matrigel. Additionally, significantly higher levels of mRNA and protein of vascular endothelial growth factor were found in ADEPCs than in RBSMCs. These results suggest the potential use of ADEPCs as angiogenic cell sources for engineering bladder tissue.